التأمين الإسلامي التكافلي في دولة الإمارات العربية المتحدة (دراسة قانونية تطبيقية) - أحمد محمد سعيد الخلفاوي
After the issuance of Insurance Authority Resolution No. (4) 2010 AD in the United Arab Emirates, with the aim of establishing a legal framework to promote the growth and development of takaful insurance, and to make the United Arab Emirates the first country in Arabia to develop regulatory legislation for the takaful industry. This decision aims to achieve the financial and legal security of the participants and ensure compliance with the Islamic Shariah requirements in Takaful operations. This study aims to clarify the takaful and commercial insurance contracts based on the objectives of Islamic law and the laws of the United Arab Emirates, as well as to show the differences between the two types of contracts. In addition, this study also discusses the legal regulations governing takaful insurance, legal compliance with it, exploring the types of takaful insurance contracts and analyzing the impact of legal requirements on the takaful insurance system as a legal model, the formation of takaful insurance contracts, such as insurers and takaful funds. This study uses descriptive methods in studying the general phenomenon of Takaful insurance and focuses on analyzing the problem as well as identifying the factors that influence it. The historical approach is also used to connect the past with the present and predict the future of Takaful insurance. In addition, field studies are also used on a group of companies that use the Takaful insurance system, as well as an induction approach to analyze the contributions of Islamic scholars in developing the Islamic Takaful insurance concept, and deductive methods are used to control and analyze texts and extract principles from Shariah sources. The results of the study found that takaful insurance is a donation contract based on unity between participants to protect their benefits from harm and achieve brotherhood and unity in the community, and is characterized by justice and balance that protects them from fraud and ignorance. There is a significant difference between the Takaful insurance contract and commercial insurance in the method of compensation, investment, established conditions. Public disclosures in the financial statements contribute to the compliance of Islamic law in takaful insurance companies. Increased operational efficiency in Takaful insurance companies plays an important role in management. The relationship between the insurer and the takaful fund is not just a profit but it is a symbiotic relationship based on Islamic law.